Pengaruh kemampuan kognitif, preferensi risiko dan gender terhadap keuntungan usaha mikro dan kecil di Indonesia - Shinta Maretadevi; Ramel Yanuarta RE (Universitas Negeri Padang, 2022)
This study aims to analyze the effect of cognitive skills, risk preferences, and gender on the profit of Micro and Small Enterprises (MSEs) in Indonesia. This study uses non-agricultural business data in the fifth Indonesian Family Life Survey (IFLS) wave. A total of 4.232 MSE met the sample criteria and were analyzed using the quantile regression method in 3 locations, 0.25, 0.50, and 0.75. This method offers a novelty analysis not only in the average but also differentiated into three quantiles representing 3 clusters of the MSE scale, the lowest 25 percent, the median, and the highest 25 percent scale of profit. From the analysis results, it can be concluded that the cognitive skills and risk preferences of MSE entrepreneurs only affect the MSE profit at highest quantile (q0.75). As for gender issues, MSEs run by male entrepreneurs generate higher profits than MSEs run by female entrepreneurs, but the difference in profits gets smaller in larger business scale quantiles. Thus, this research practically implies that a different strategy is needed in developing MSE in the future.Keywords: Micro and small enterprises, cognitive skills, risk preference, gender, quantile regression.